The Comparative Effect Between Pellets and Porridge Made from Local Ingredients on Body Weight of Rats with Protein-Energy Deficiency - Dandi Sanjaya; Dono Indarto; Ida Nurwati (Proceedings of the International Conference on Nursing and Health Sciences, 2023)
Protein-energy deficiency (PED) is a major infant health problem in developing countries with high mortality rate. Inadequate food intake and infectious diseases are the main factors for PED. In clinical setting, branded foods are commonly used to treat the PED but these foods are expensive. Canna (Canna edulis Ker.), catfish (Pangasius sp.), and red beans (Phaseolus vulgaris) are easily found in Indonesia and rich carbohydrates and protein. Therefore, this study aimed to compare the effect between pellets and porridge from canna, catfish, and red beans (GANIME) on the body weight (BW) of rats with PED.Ten male wistar rats, which aged 3 weeks and weighed 50-100 g, were used in this in vivo study. The rats model with PED was made by using the existing method through 40-60% gradual feed restriction for 14 days. Selected rats were randomly divided into 2 groups: G1 was given GANIME pellets and G2 was given GANIME porridge for 14 days. The rat BW each group routinely weighed every 7 days.The average BW of G1 rats was 78,00 ± 15,52 g, which was not significant different from the average BW of G2 rats was 70,50 ± 2,12 g (p= 0,64). In group G1 there was a greater increase than in group G2, namely 12.67 grams.Administration of GANIME pellets increases more body weight in rats with PED, compared to administration of GANIME porridge.